Long-term Correction of Very Long-chain Acyl-CoA Dehydrogenase Deficiency in Mice Using AAV9 Gene Therapy - Keeler, Allison M (Nature Publishing Group, 2012)
Very long-chain acyl-coA dehydrogenase (VLCAD) is the rate-limiting step in mitochondrial fatty acid oxidation. VLCAD-deficient mice and patients clinical symptoms stem from not only an energy deficiency but also long-chain metabolite accumulations. VLCAD-deficient mice were treated systemically with 1 × 10(12) vector genomes of recombinant adeno-associated virus 9 (rAAV9)-VLCAD. Biochemical correction was observed in vector-treated mice beginning 2 weeks postinjection, as characterized by a significant drop in long-chain fatty acyl accumulates in whole blood after an overnight fast. Changes persisted through the termination point around 20 weeks postinjection. Magnetic resonance spectroscopy (MRS) and tandem mass spectrometry (MS/MS) revealed normalization of intramuscular lipids in treated animals. Correction was not observed in liver tissue extracts, but cardiac muscle extracts showed significant reduction of long-chain metabolites. Disease-specific phenotypes were characterized, including thermoregulation and maintenance of euglycemia after a fasting cold challenge. Internal body temperatures of untreated VLCAD(−/−) mice dropped below 20 °C and the mice became lethargic, requiring euthanasia. In contrast, all rAAV9-treated VLCAD(−/−) mice and the wild-type controls maintained body temperatures. rAAV9-treated VLCAD(−/−) mice maintained euglycemia, whereas untreated VLCAD(−/−) mice suffered hypoglycemia following a fasting cold challenge. These promising results suggest rAAV9 gene therapy as a potential treatment for VLCAD deficiency in humans.